Factores predictores del abandono de la intervención psicológica grupal en una muestra de pacientes con cáncer de mama - Sánchez, Nuria; Torres, Ana; Camprubí, Natalia; Vidal, Ángela; Salamero, Manel (Psicooncología, 2005)
Between these To examine the socioeconomic, medical and coping factors that may predict dropping out of group psychotherapy in a sample of women recently diagnosed of breast cancer. 62 breast cancer patients undergoing oncologic treatment and attended a group psychotherapy program were included in the study. In the assessment interview we obtained information about their socioeconomic and clinical situation. During the first group session, a battery of questionnaires (COPE, GHQ-12, EORTC-QLQ-C-3.0) we administered to the participants. Patient assistance to the sessions was registered throughout the treatment. The sample was divided into 2 groups at the end of treatment: patients who had completed the therapy (assistance to a minimum of 60% of the sessions) and those who did not reach this threshold of assistance. The differences 2 groups were analysed and logistic regression with significant variables in bivariant analysis was performed. Drop out rate observed in the study was 27’5%. Higher educational level and the use of planning as a coping strategy were associated with better psychotherapy compliance in the logistic regression model. Age, psychopathological state and quality of life did not show significance as predictors of dropping out of treatment. Educational level and coping strategies are important factors to take into account in further studies about drop out rates in group psychotherapies for cancer patients.
Keywords: Breast cancer; Dropout of psychological treatment; Adherence of psychological treatment; Coping strategies